Case report: Active clinical manifestation of endocardial fibroelastosis in adolescence in a patient with mitral and aortic obstruction–histologic presence of endothelial-to-mesenchymal transformation - Diaz-Gil, Daniel; Carreon, Chrystalle Katte; Silva-Gomez, Natalia; Benheim, Alan E.; Emani, Sitaram M.; del Nido, Pedro J.; Marx, Gerald R.; Friehs, Ingeborg (Frontiers in Cardiovascular Medicine, 2022)
This is the first description of active clinical manifestation of endocardial fibroelastosis (EFE) and remodeling of the endocardium via endothelial-to-mesenchymal transformation (EndMT) in an adolescent with Shone’s variant hypoplastic left heart complex (HLHC) and a genetic heterozygous ABL1 variant. While EFE has not been typically associated HLHC or Shone’s syndrome, in this patient flow alterations in the left ventricle (LV), combined with genetic alterations of intrinsic EndMT pathways led to active clinical manifestation of EFE in adolescence. This case emphasizes that new therapies for EFE might need to focus on molecular factors influenced by intrinsic and extrinsic stimuli of EndMT.